On the application of photocatalyst-sorbent composite materials for arsenic(III) remediation: Insights from kinetic adsorption modelling. Issue 5 (October 2020) - Bullen, Jay C.; Lapinee, Chaipat; Salaün, Pascal; Vilar, Ramon; Weiss, Dominik J.
Highlights: High photocatalyst-sorbent concentrations are required for arsenic(III) removal. Adsorption kinetic models predict batch treatments are superior to continuous-flow. Photocatalyst-sorbent reactors will require regular replacement of the media. Graphical abstract: Abstract: TiO2 –Fe2 O3 composites show great promise for the removal of arsenic(III) from drinking water: this single material combines the photocatalytic capabilities of TiO2 for the oxidation of arsenite (i.e. As(III)) with the high adsorption capacity of iron oxides towards the arsenate (i.e. As(V)) subsequently produced. To design an effective treatment, it is necessary to balance high sorbent concentrations, providing long filter lifetimes, with low photocatalyst concentrations, to achieve effective penetration of light into the system. In this work, we construct a predictive model using experimentally determined As(III) adsorption isotherms and kinetics to estimate arsenic treatment plant lifetimes. We considered sorbent loading, treatment time, and batch treatment versus continuous-flow. Our model indicated that batch treatment is more efficient than continuous-flow at low sorbent concentrations (<100 g L −1 ), and therefore more appropriate for the photocatalyst-sorbent system. However, with <100 g L −1 sorbent, media should be replaced several times per year to maintain effective treatment. In contrast, slurries of >100 g L −1 sorbent could operate for an entire year without media replacement. This work highlights the important implications of sorbent concentration when we consider the multifunctional photocatalysts-sorbent system, and highlights the need for further experimental work to design efficient arsenic treatment plants.